Impactos ambientais de cemitérios: estudo de caso em um município no semiárido do Brasil - Morais, Geversson Pinheiro Dias Fernandes de (Universidade Federal Rural do Semi-Árido, 2019)
Cemeteries are characterized by great sources of environmental impact, which refer to physical, chemical, biological and anthropic dimensions. In the study in question, the objective was to evaluate the environmental impact scenarios in the cemeteries of São Manoel and Parque da Saudade, both located in the city of Pau dos Ferros - Rio Grande do Norte, Brazil. Based on the collection of technical collections and current legislation, an exploratory and descriptive research was based on the areas of the necropolis and its surroundings, as well as the perception of the residents who live nearby and of the gravediggers of the projects. The characterization of the area was also elaborated through the information of the databases in organs responsible for the maintenance of the cemeteries in the city, such as the survey in loco, besides contemplating the estimate of the necrochorume production. From the identified circumstance were proposed methods and techniques aimed at promoting the mitigation of the observed impacts. This led to the presence of risks to the environment and the population. The original result was the measures regarding environmental mitigation of reference to the cemeteries, whether structural or administrative, aimed at the management and control of such actions, with the intention that they may have in-depth technical feasibility study for application to the municipality.
Keywords: Necrópoles Resíduos sólidos Necrochorume Percepção ambiental Medidas mitigadoras; Necropolis Solid waste Necrochorume Environmental perception Mitigating measures; ENGENHARIAS::ENGENHARIA SANITARIA